The Effect of Administration of Ginger Decil Water on Reduce the Levels of Disminore Pain in Adolescent Women at SMAN 03 Bengkulu City - Mika Oktarina; Nuril Absari; Choralina Eliagita; Nurobikha Nurobikha; Guina Iga Agtivani (CV Media Inti Teknologi, 2023)
Dysmenorrhea is pain during menstruation where almost more than 50% of women experience it. Women in Indonesia who experience dysmenorrhea mostly overcome it by taking painkillers which can lead to dependence and negative effects. The purpose of this research is to study the effect of giving ginger water decoction to reducing the level of dysmenorrhea pain in young women in SMAN 03 Bengkulu City. This study uses a quasi-experimental approach with designone Group pre and post-test design. The population in this study were 122 students of SMA Negeri 03 Bengkulu City, grades X and XI who experienced dysmenorrhea. Sampling in this study used a purposive sampling technique of 16 female students. The data used is primary data. Data were analyzed using univariate and bivariate analysis with the Shapiro Wilk test and Wilcoxon Sign Rank test. The results of the study were obtained from 16 samples the average value of pain for the sample group before being given ginger decoction was 4.38 and for the group after being given ginger decoction was 3.38. Analysis results Wilcoxon Sign Rank Test obtained a value of z = -5.85 with a value of p = 0.000 < a = 0.05, so it was found that there was an effect of giving ginger water decoction to reducing the level of dysmenorrhea pain in young women at SMAN 03 Bengkulu City. It is hoped that the school can work together with health workers in providing information about the benefits of ginger water decoction for menstrual pain, so that students' knowledge increases and can reduce dysmenorrhea pain when menstruation occurs.